2018
DOI: 10.1039/c8cc02994f
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the spin-related transport properties of FePc on Au(111) through single-molecule chemistry

Abstract: Tuning the spin-dependent electron transport through molecules is of fundamental importance in single-molecule spintronics. Here, the transport properties of iron phthalocyanine on Au(111) was investigated by a combination of scanning tunneling microscopy and density functional theory calculations. Using high-resolution scanning tunneling spectroscopy performed at 0.5 K, a Kondo resonance was observed on FePc. After removing its eight outermost hydrogen atoms, the spectroscopic feature changed into a double-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
1
17
0
1
Order By: Relevance
“…The rich functionalities of porphyrin complexes orginate from the center macrocycle, which can stablize a variety of elements inside and thus gives rise to distinct structural, electronic, magnetic, optoelectronic, and transport properties [4][5][6][7][8][9][10][11][12][13] . Magnetic metalloporphyrins have been extensively studied by various techniques, exhiting kondo and spin excitation effects, Yu-Shiba bound states, and spin-state switching [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] . Recently, hybridized graphene and metalloporphyrin nanostructures have been achieved, hosting combined intriguing electronic and magnetic properties [28][29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…The rich functionalities of porphyrin complexes orginate from the center macrocycle, which can stablize a variety of elements inside and thus gives rise to distinct structural, electronic, magnetic, optoelectronic, and transport properties [4][5][6][7][8][9][10][11][12][13] . Magnetic metalloporphyrins have been extensively studied by various techniques, exhiting kondo and spin excitation effects, Yu-Shiba bound states, and spin-state switching [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] . Recently, hybridized graphene and metalloporphyrin nanostructures have been achieved, hosting combined intriguing electronic and magnetic properties [28][29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…A clear Kondo resonance and a high Kondo temperature of 200 K were observed. The dehydrogenation threshold voltage applied was found in the range of 3.3 V to 3.5 V. In the case of a FePc molecule adsorbed on Au(111), cutting away its eight outermost hydrogen atoms by applying a −3.5 V voltage pulse turned off the Kondo effect . The formation of the chemical bonds between the dehydrogenated CoPc molecule and Au atoms of the surface increased the distance between the Fe 2+ ion and the Au atoms, thereby weakening the Fe–Au coupling.…”
Section: Unimolecular Reactions: Chemical Bond Dissociationmentioning
confidence: 99%
“…Thedehydrogenation threshold voltage applied was found in the range of 3.3 Vto3.5 V. In the case of aF ePc molecule adsorbed on Au(111), cutting away its eight outermost hydrogen atoms by applying a À3.5 Vv oltage pulse turned off the Kondo effect. [59] Thef ormation of the chemical bonds between the dehydrogenated CoPc molecule and Au atoms of the surface increased the distance between the Fe 2+ ion and the Au atoms,thereby weakening the Fe-Au coupling.C onsequentially,t he molecule changed from the Kondo state to the magnetic triplet state.K im et al demonstrated that the spin state of Co-porphyrin on Au(111) could be reversibly switched by binding and releasing the NO molecule. [60] TheK ondo effect was switched off by the formation of the coordination complex NO-Co-porphyrin, and could be switched back on by removing the NO by local manipulation or thermal desorption (at 500 K).…”
Section: Electron Injectionmentioning
confidence: 99%
“…Molecular spintronics has attracted tremendous attentions due to its promising applications in nanoelectronics in the past few years [1,2,3,4,5,6]. The conductance can be directly controlled by the spin degrees of freedom in a single molecule.…”
Section: Introductionmentioning
confidence: 99%